Pengaruh Kualitas Produk dan Kualitas Layanan terhadap Kepuasan Konsumen Shopee - Bunga Citra Lestari; Bainun Maulana Assyaf; Reda Ebadi Qamar; Khilwah ‘Ainizzahwa; Eteh Resa Asyifa (Yayasan Literasi Sains Indonesia, 2026)
Consumer satisfaction is defined as a feeling of pleasure or disappointment that arises from a comparison between the performance of products and services received and prior expectations. This research employs a quantitative approach with an associative method to examine the relationships and influences among variables. Primary data were collected through an online questionnaire using a Likert scale distributed to Shopee users. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, preceded by validity and reliability tests as well as classical assumption tests, and followed by t-tests and an F-test. The results indicate that all research instruments are valid and reliable, and the regression model meets the assumptions of normality and absence of multicollinearity. Partially, both product quality and service quality have a positive and significant effect on consumer satisfaction. Simultaneously, product quality and service quality also have a significant effect on consumer satisfaction. Furthermore, the findings reveal that service quality has a more dominant influence than product quality. These results suggest that improving product quality and, in particular, service quality is crucial for enhancing consumer satisfaction and creating a positive shopping experience on e-commerce platforms.